Likelihood Ratios for the Emergency Physician. (19th July 2018) - Peng, Paul; Coyle, Andrew
Abstract: The concept of likelihood ratios was introduced more than 40 years ago, yet this powerful metric has still not seen wider application or discussion in the medical decision‐making process. There is concern that clinicians‐in‐training are still being taught an oversimplified approach to diagnostic test performance and have limited exposure to likelihood ratios. Even for those familiar with likelihood ratios, they might perceive them as mathematically cumbersome in application, if not difficult to determine for a particular disease process. This article takes a conceptual approach to likelihood ratios and applies them to two clinical settings: 1) severe intracranial injury after minor head trauma and 2) suspected pulmonary embolism with shortness of breath. Likelihood ratios are the most appropriate metric for efficient rational clinical examination and can prevent unnecessary and wasteful treatments and procedures.